Long-Term Prognostic Role of Computed Tomography Coronary Angiography for Stable Angina - Meah, Mohammed N. (Curr Treat Options Cardiovasc Med, 2020)
PURPOSE OF REVIEW: Chest pain is a common presentation, and there are a wide variety of ways in which it can be investigated and treated. There is growing interest in whether the way we reach a diagnosis of angina can affect the long-term prognosis. In addition to its unparalleled negative predictive value, computed tomography coronary angiography (CCTA) gives anatomical information on the extent and severity of coronary artery disease. This article discusses recent research into the ability of CCTA to predict and improve long-term prognosis for patients with stable angina. RECENT FINDINGS: Results from retrospective studies, randomised controlled trials and meta-analyses all suggest that initial investigation with computed tomography coronary angiography confers a prognostic benefit. In addition, the most recent studies have shown that the assessment of plaque burden and plaque constituents is predictive of long-term outcomes. SUMMARY: Management of stable chest pain should be guided by a CCTA-based approach. Future research should focus on whether incorporating plaque analysis strategies into clinical practice confers additional benefit.